The Effect of Job Crafting and Career Adaptability on Job Performance Mediated by Psychological Availability in Bank Papua - Pala'langan, Yulianus Adi; Satrya, Aryana (International Journal of Social Service and Research, 2023)
Job performance is the highlight and benchmark for every organisation. It is directly related to the organisation, thus generating value and contributing to the organisation's goals, which are demonstrated in the organisation's financial and non-financial results. Optimal individual job performance will lead to business success and affect organisational profitability. This study aims to examine the effect of job crafting and career adaptability on job performance and the indirect effect through the mediation of psychological availability. Empirical data were collected from 220 Bank Papua employees using an online survey method. This study was analysed using Structural Equation Modeling (SEM) and confirmatory factor analysis to test the proposed hypotheses. Lisrel software was used to analyse and test the seven hypotheses created based on the research model. The results showed that career adaptability has a positive effect on job performance both directly and through the mediation of psychological availability. However, job crafting was found to have a negative effect on job performance. Furthermore, this research is expected to contribute to human resource literature, especially for policy makers and related parties to pay attention to aspects of career adaptability, which play a role in the process of shaping employee performance.